Animals through Chinese History Earliest Times to 1911 - Sterckx, Roel; Siebert, Martina; Schäfer, Dagmar (Social Sciences, 2018)
This volume opens a door into the rich history of animals in China. Drawing on an extensive array of primary sources, the essays explore not only developments in the human-animal relationship but the ways in which the Chinese have thought about the world with and through animals. This title is also available as Open Access.